Aloe polymeric acemannan inhibits the cytokine storm in mouse pneumonia models by modulating macrophage metabolism. (1st December 2022) - Li, Lu; Xu, Weijie; Luo, Yinzhu; Lao, Chunqin; Tong, Xueli; Du, Junxi; Huang, Bihong; Li, Di; Chen, Jingmian; Ye, Huiling; Cong, Feng; Guo, Xiaofeng; et al.
Abstract: The cytokine storm is highly associated with inflammatory-type disease severity and patients' survival. Plant polysaccharides, the main natural phytomedicine source, have a great potential to be an effective drug to treat cytokine storm. Herein we found that a polymeric acemannan (ABPA1) isolated from Aloe Vera Barbadensis extract C (AVBEC) exerted prominent inhibitory effects on inflammation-induced cytokine storm. The results displayed that ABPA1 effectively suppressed LPS-induced proinflammatory cytokines release in vitro . Moreover, ABPA1 treatment alleviated the cytokine storm and tissue damage in LPS- and IAV-induced mouse pneumonia models, and altered the phenotypic balance of macrophages in lung tissues. Functionally, ABPA1 enhanced macrophage M2 polarization and phagocytosis in RAW264.7 cells and inhibited LPS-induced M1 polarization. Mechanistically, ABPA1 enhanced mitochondrial metabolism and OXPHOS through activated PI3K/Akt/GSK-3β signalling pathway. Overall, our findings suggest that ABPA1 may modulate macrophage activation and mitochondrial metabolism by targeting PI3K/Akt/GSK-3β signalling pathway, thereby alleviating cytokine storm and inflammation. Graphical abstract: Unlabelled Image